Studies in macroeconomic theory : volume 2, redistribution and growth - Phelps, Edmund S. (New York : Academic Press, 1980)
This publication is a collection of the authors scholarly papers on the behavior and public control of distribution and growth in the market economy.
Includes bibliographical references.
gp 24/01/2019
Loans
Keywords: Macroeconomics